2020
DOI: 10.1152/ajpcell.00152.2019
|View full text |Cite
|
Sign up to set email alerts
|

Zinc is essential for the transcription function of the PGC-1α/Nrf2 signaling pathway in human primary endometrial stromal cells

Abstract: Zinc (Zn) has antioxidant effect in different types of organs and is closely associated with human health. Endometrial receptivity is one of the most important factors in the embryo implantation and development. However, the regulatory mechanism of Zn in endometrium tissue is still unclear. In the study, we found that plasma Zn level is significantly associated with female infertility, which severely affects female reproductive health. Primary endometrial stromal cells were isolated from female endometrium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In vitro and in vivo experiments proved that enhanced AMPK/PGC-1α signaling pathway activity and PGC-1α expression protect RGCs in the RGC-5 cell line, rat primary RGCs, and rat chronic ocular hypertension models ( Chen S. et al, 2013 ; Zhang et al, 2018 ; Uchida et al, 2019 ). A recent study showed that zinc is essential for PGC-1α transcription and increases antioxidant stress in human primary endometrial stromal cells ( Lu et al, 2020 ). However, more research is needed to elucidate the role of zinc in PGC-1α signaling in neurons and RGCs.…”
Section: Mitochondria Of Rgcs: Critical Target Of Metal Ionsmentioning
confidence: 99%
“…In vitro and in vivo experiments proved that enhanced AMPK/PGC-1α signaling pathway activity and PGC-1α expression protect RGCs in the RGC-5 cell line, rat primary RGCs, and rat chronic ocular hypertension models ( Chen S. et al, 2013 ; Zhang et al, 2018 ; Uchida et al, 2019 ). A recent study showed that zinc is essential for PGC-1α transcription and increases antioxidant stress in human primary endometrial stromal cells ( Lu et al, 2020 ). However, more research is needed to elucidate the role of zinc in PGC-1α signaling in neurons and RGCs.…”
Section: Mitochondria Of Rgcs: Critical Target Of Metal Ionsmentioning
confidence: 99%
“…Zinc can stabilize the Zn-finger domain of NF-κB [ 148 ] where it acts as an alternative inhibitor of IKB [ 149 ]. As a transcription regulator of Nrf2, it can upregulate some downstream antioxidants through nuclear translocation and thus respond to damage caused by ROS [ 150 ]. Zinc, together with copper, is a cofactor for one of the most important antioxidant enzymes, Zn-SOD/SOD1 [ 151 ], which has a crucial role in women’s ovulation and menstrual cycles by scavenging ROS [ 152 ].…”
Section: Antioxidant Systems In Female Reproductionmentioning
confidence: 99%
“…Comparing the long and short-terms morbidity of laparoscopic myomectomy (even without LUAO), the study modified the Jadad score to assess the quality of Randomized controlled trials (RCTs) but employed methodologic index for nonrandomized studies to evaluate the quality of observational studies (OSs). symptomatic uterine myomas, two independent researchers in Liu, Lu 16 carried out data selection to perform a comparative study of the clinical outcomes of uterine artery embolization and those of high-intensity focused ultrasound (HIFU) ablation in women with myomas. The study quality was assessed using the "Cochrane Handbook for Systematic Reviews" while the pooled mean difference and relative risks were both calculated at 95% confidence interval for the respective continuous data and dichotomous data.…”
Section: Past Related Workmentioning
confidence: 99%